Search for a Standard Model Higgs Boson in WH -> lvbb in pp Collisions at s=1.96 TeV - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We present a search for a standard model Higgs boson produced in association with a W boson using 2.7fb-1 of integrated luminosity of pp̄ collision data taken at s=1.96TeV. Limits on the Higgs boson production rate are obtained for masses between 100 and 150GeV/c2. Through the use of multivariate techniques, the analysis achieves an observed (expected) 95% confidence level upper limit of 5.6 (4.8) times the theoretically expected production cross section for a standard model Higgs boson with a mass of 115GeV/c2. © 2009 The American Physical Society.